Runx2 Suppresses Astrocyte Activation and Astroglial Scar Formation After Spinal Cord Injury in Mice - Leilei Lu; Jiazong Ye; Dafa Yi; Tengfei Qi; Tong Luo; Silei Wu; Liangliang Yang; Lei Li; Hongyu Zhang; Daqing Chen (Molecular Neurobiology, 2024)
After spinal cord injury, astrocytes undergo a reactive process and form an astroglial scar, which impedes the regeneration of axons. The role of Runx2 in promoting the transformation of astrocytes in the central nervous system is well-established. However, it remains unclear whether Runx2 also plays a role in the development of astroglial scar, and the precise underlying mechanism has yet to be identified. Recently, our study using cell culture and animal models has demonstrated that Runx2 actually suppresses astrocyte activation and the formation of astroglial scar following injury. The initial results demonstrated an increase in the expression of Runx2 in astrocytes following in vivo injury. Subsequently, the overexpression of Runx2 resulted in the inhibition of astrocyte activation, reduction in the total area of astroglial scar, and restoration of neural function after 14 days of injury. However, these effects were reversed by CADD522. These findings indicate that Runx2 could potentially serve as a therapeutic intervention for spinal cord injury (SCI). Furthermore, our findings suggest that the Nuclear-matrix-targeting signal (NMTS) of Runx2 is associated with its effect. In summary, the study’s results propose that targeting Runx2 may be a promising treatment approach for reactive astrocytes and astroglial scar in the recovery of SCI. Graphical Abstract